Remote detection of radioactive hotspot using a Compton camera mounted on a moving multi-copter drone above a contaminated area in Fukushima. Issue 6 (2nd June 2020) - Sato, Yuki; Ozawa, Shingo; Terasaka, Yuta; Minemoto, Kojiro; Tamura, Satoshi; Shingu, Kazutoshi; Nemoto, Makoto; Torii, Tatsuo
ABSTRACT: The Fukushima Daiichi Nuclear Power Station (FDNPS), operated by Tokyo Electric Power Company Holdings, Inc., suffered a meltdown as a result of a large tsunami triggered by the Great East Japan Earthquake on 11 March 2011. To proceed with environmental recovery, a radiation distribution map that indicates the distribution of radioactive substances is extremely important to establish detailed decontamination plans. We developed a remote radiation imaging system comprising a lightweight Compton camera mounted on a multi-copter drone to measure the distribution of radioactive substances remotely. The proposed system can perform radiation imaging using the Compton camera while flying and moving. In addition, the distribution of radioactive substances can be visualized three-dimensionally by drawing the radiation images captured by the Compton camera on a three-dimensional (3D) topography model acquired by a 3D-LiDAR (Light Detection and Ranging) system. We conducted a survey of radioactive hotspots in difficult-to-return zones in the coastal area of Fukushima, Japan. The drone system realized 3D visualization of several hotspots. Such remote technology would be useful for monitoring the difficult-to-return zone as well as for monitoring the distribution of radioactive substances inside the FDNPS site where decommissioning work is ongoing.